Peran Pemerintah Dalam Mengurangi Perdagangan Narkoba Dengan Memanfaatkan Teknologi. - Askarmin; Timbul Dompak (Prodi Ilmu Administrasi Negara, 2024)
Drug trafficking is a serious problem that continues to threaten public security and health. The government is required to develop a more effective strategy in overcoming this problem, one of which is by utilizing technology. This research aims to evaluate the role of the BOSS (BNN One Stop Service) application as a tool to help the government in reducing drug trafficking. The research methods used include collecting primary and secondary data through literature studies, searching for various related information, as well as analyzing drug case data obtained from the BOSS application. The research results show that the BOSS application is able to increase the effectiveness of monitoring and preventing drug trafficking through integrated data collection and analysis. This application not only enables early detection of suspicious activity, but also increases public participation in anonymous reporting, thereby expanding the scope of surveillance. These findings indicate that the use of technology in the BOSS application has great potential to strengthen government efforts to tackle drug trafficking and create a safer environment.